Atomistic simulations of PdTi high-temperature shape-memory alloys. (November 2018) - Ko, Won-Seok; Jeon, Jong Bae
Abstract: Martensitic phase transformations in palladium-titanium high-temperature shape-memory alloys (HTSMA) are studied using molecular dynamics simulations. On the basis of the second nearest-neighbor modified embedded-atom method formalism, an interatomic potential for the binary palladium-titanium system is determined by improving the unary descriptions of pure palladium. The developed interatomic potential accurately reproduces physical properties at the equiatomic composition and the resultant temperature- and stress-induced phase transformations between B2 austenite and B19 martensite structures. Subsequent large-scale molecular dynamics simulations demonstrate that the developed potential can be successfully utilized to investigate atomic details of phase transformations in nanocrystalline palladium-titanium alloys. Highlights: An interatomic potential for the palladium-titanium high-temperature shape-memory alloys is now available. Temperature- and stress-induced martensitic phase transformations are studied using molecular dynamics simulations. Nanocrystalline cells indicate the full recovery of the initial structure after thermal and mechanical cyclic loadings.